9(3n+5)=6(7n+5)+2

Simple and best practice solution for 9(3n+5)=6(7n+5)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3n+5)=6(7n+5)+2 equation:


Simplifying
9(3n + 5) = 6(7n + 5) + 2

Reorder the terms:
9(5 + 3n) = 6(7n + 5) + 2
(5 * 9 + 3n * 9) = 6(7n + 5) + 2
(45 + 27n) = 6(7n + 5) + 2

Reorder the terms:
45 + 27n = 6(5 + 7n) + 2
45 + 27n = (5 * 6 + 7n * 6) + 2
45 + 27n = (30 + 42n) + 2

Reorder the terms:
45 + 27n = 30 + 2 + 42n

Combine like terms: 30 + 2 = 32
45 + 27n = 32 + 42n

Solving
45 + 27n = 32 + 42n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-42n' to each side of the equation.
45 + 27n + -42n = 32 + 42n + -42n

Combine like terms: 27n + -42n = -15n
45 + -15n = 32 + 42n + -42n

Combine like terms: 42n + -42n = 0
45 + -15n = 32 + 0
45 + -15n = 32

Add '-45' to each side of the equation.
45 + -45 + -15n = 32 + -45

Combine like terms: 45 + -45 = 0
0 + -15n = 32 + -45
-15n = 32 + -45

Combine like terms: 32 + -45 = -13
-15n = -13

Divide each side by '-15'.
n = 0.8666666667

Simplifying
n = 0.8666666667

See similar equations:

| 2x+3(35-x)=92 | | .4x+x=63 | | 0.8x-5.9=0.5 | | 4(x+1)+7=4 | | T-8b=3 | | 7h=5h+8 | | 4j+2= | | (X+11)(X+1)= | | x-20=-80 | | 14x+17=1000 | | 0.3(2x+16)=0.6(x+8) | | 90=2*15+2*W | | 4(x-1)=11+3 | | -5x+20=5x+20 | | -2x-1=-7x+4y | | 1000(8x-10)=50(562+100x) | | 14x+17=80 | | 7y+2(y-3)=4(y+1)-3 | | 200x+4x=450 | | -5(x+7)=25 | | -60z-0.7=-70z+1.8 | | Y-13= | | 5h=8.5 | | 3.7*4.9=18.13 | | y=a(x+2)(2x+10) | | 17x+43x-16=10(6x+17) | | 3.7*4.9= | | -0.4+0.4+0.6x=0.9-0.3x | | 2x^2-7x+4= | | 14x+294=7 | | 5x-x=-5 | | 2+22=-4(4x-6) |

Equations solver categories